Early surgical intervention for patients with possible clinically silent somatotroph adenoma: a case series - Kawaguchi, Tomohiro (J Med Case Rep, 2019)
INTRODUCTION: Clinically silent somatotroph adenoma is characterized by elevated serum growth hormone but without the clinical symptoms of acromegaly, and it is considered rare. The natural history is not well understood, progress to symptomatic is uncertain, and treatment strategy has not been established. CASE PRESENTATION: The first patient was a 48-year-old-Asian woman who presented with serum growth hormone 6.99 ng/ml and insulin-like growth factor 1 of 476 ng/ml, but no characteristic features of acromegaly. Five years after initial diagnosis, she presented with acromegalic facial appearance. Transsphenoidal surgery achieved gross total removal and endocrinological remission. The second patient was a 40-year-old-Asian woman who presented with serum growth hormone 31.14 ng/ml and insulin-like growth factor 1 of 709.6 ng/ml, but no characteristic features of acromegaly. Three years after initial diagnosis, she presented with acromegalic facial appearance. Transsphenoidal surgery achieved gross total removal and endocrinological remission. The third patient was a 64-year-old-Asian woman who presented with serum growth hormone 6.0 ng/ml and insulin-like growth factor 1 of 341 ng/ml, but no characteristic features of acromegaly. Eight months after initial diagnosis, hand enlargement was detected. Transsphenoidal surgery achieved gross total removal and endocrinological remission. CONCLUSION: Due to its potential for evolving to symptomatic disease, the risks of surgery and observation for patients with somatotroph adenoma should be carefully compared from the viewpoint of better health outcome.